Production of Î²-Galactosidase from Lactobacillus cultures applying different extraction techniques - Hati, Subrota (Indian Journal of Dairy Science, 2017)
In this study, nine Lactobacillus cultures i.e. Lactobacillus helvieticus (V3), Lactobacillus rhamnosus (NK2), Lactobacillus casei (NK9), Lactobacillus rhamnosus (NK10), Lactobacillus fermentum (M5), Lactobacillus paracasei(M16), Lactobacillus rhamnosus (M31), Lactobacillus plantarum (M38) and Lactobacillus pentosus(M22) were evaluated for the production of Î²-Galactosidase enzyme. Ultrasonication alone or in a combination with lysozyme and SDS-chloroform treatment was used to rupture the cell wall to release the Î²-Galactosidase enzymes. On comparing different methods used for Î² galactosidase extraction from nine different cultures, sonication method was found to be more effective for Lactobacillus fermentum (M5) and Lactobacillus helveticus (V3) whereas Lysozyme-EDTA method proved optimum for Lactobacillus helveticus (V3) and Lactobacillus rhamnosus (NK10) and SDS-chloroform method was found better for Lactobacillus pentosus (M22) and Lactobacillus plantarum (M38) for the Î²-Galactosidase production. The combine method of SDS-chloroform and sonication was found to be more effective for Lactobacillus plantarum (M38) and Lactobacillus fermentum (M5) whereas Lysozyme-EDTA along with sonication proved best for Lactobacillus rhamnosus (NK2) and Lactobacillus rhamnosus (NK10).